The sum of Lagrange numbers - Gaster, Jonah; Loustau, Brice (Proceedings of the American Mathematical Society, 2021)
Combining McShane’s identity on a hyperbolic punctured torus with well-known geometric interpretations of the Markov Uniqueness Conjecture (MUC), we find that MUC is equivalent to the identity ∑n=1∞(3−Ln)=4−φ−2, where Ln is the nth Lagrange number and φ=1+52 is the golden ratio.
Gesehen am 21.02.2022